Tipos de resistência a Alabama Argillacea (Huebner, 1818) (Lepidoptera: Noctuidae) envolvidos em genótipos de algodoeiro: II. Antibiose - Ferreira, Alvemar [UNESP]; Lara, Fernando Mesquita [UNESP] (FapUNIFESP (SciELO), 1999)
Cotton genotypes resistance to Alabama argillacea (Huebner, 1818) due to antibiosis has been evaluated in laboratory trials (at 27 ± 2°C, 70 ± 10% relative humidity and 14 hours photoperiod). Six different genetic materials (T 1122-13-1, STO 285 N, JPM 157, T 953-13-4-2, CNPA 9211-21, and CNPA 9211-31) have been tested in a completely randomized experimental design, with ten replications, each one with ten larvae/genotype. Larvae have been supplied with leaves daily. The following variables have been scored: time length of several insect stages (from larvae to adult), average mass of larvae and pupae as well as average larval, pre-pupal and pupal mortality rates. All genotypes have revealed longer overall average time length of stage duration from larvae to adult, as compared to STO 285 N; however, CNPA 9211-31 and CNPA 9211-21 have shown the smallest average mass of pupae along with high frequencies of pre-pupae and larvae to adult mortalities. The results strongly suggest that antibiosis is one of the resistance mechanisms to A. argillacea in that two cotton genotypes.
Evaluation of cotton genotypes resistance to Alabama Argillacea (Huebner, 1818) (Lepidoptera: Noctuidae): II. Antibiosis
Keywords: cotton; genotype; pest resistance; Alabama argillacea; Gossypium hirsutum; Insecta; Lepidoptera; Noctuidae